Minimization of Localization Error using Connectivity based Geometrical Method in Wireless Sensor Networks - Sita Kumari. CH; Dr. S.P. Setty (International Journal of Engineering and Management Research, 2018)
Many localization schemes are designed for finding the geographical coordinates of the unlocalized node in the network. Still, it is a difficult problem to find accurate and efficient localization schemes in the Wireless Sensor Networks (WSNs). We proposed a new method, connectivity based WSN node localization using one of the geometrical method namely centroid of a triangle. By developing the centroid of a triangle from the WSN network model in terms of localization requirements. The simulation outcomes have shown that the modified centroid (centroid_T) performs marginally better than the existing centroid method with a marginally increase in the computation process. We also observe the variation of localization error with various anchor nodes, radio range, and network size.